(untitled) (International Journal of Environmental Sciences, 2025)
Unani medical experts both classical and modern have developed various methods for determination of the human temperament called “mizaj” in Unani terminology. The present research proposes to develop a temperament classification system where individual temperament based on the fundamentals of Unani medical science can determined from the subject or patient available data, the temperament can be validated by human expertise, machine intelligence and modern technologies. In this paper, computational and mathematical modelling have been applied to determine the Unani temperament. The derived model can be validated and calibrated using real data to make it more robust. The model can be converted into an algorithm and can be integrated into a health care system using modern data analytics approaches.